Analisis Pengaruh Label Ramah Lingkungan Terhadap Keputusan Pembelian Produk Ramah Lingkungan - Robetmi Jumpakita Pinem; Nurul Imani Kurniawati; Riandhita Eri Werdani Werdani (Faculty of Economics and Business Diponegoro University, 2018)
Concern for the environment is a must for everyone because the issue of environmental damage is what we have often heard from various media, even from the community or mouth to mouth, how important it is for everyone to pay attention to environmental sustainability. very important information to educate consumers about being environmentally friendly. Through eco-friendly labels listed on a product indirectly it will increase public knowledge about products that are environmentally friendly. This study is a descriptive study that aims to provide an overview or explanation of the conditions or situations of the variables studied in the community. Respondents in this study were 50 students. Primary data collection is done through the distribution of questionnaires to respondents and secondary data through literature studies in the form of books, magazines and reports of research results that have been done before. Data was tested using simple linear regression method statistics with the help of SPSS version 20 software.It can be concluded that eco-friendly labels are very important as a valid sign from the government of environmentally friendly products. About 98% of eco-friendly labels can influence purchasing decisions on environmentally friendly products, only 2% outside the variables studied affect purchasing decisions for environmentally friendly products.